Hospital Recommendation and Mapping System Using Analytical Hierarchy Process Method and Dijkstra Algorithm Based on Website - Tri Ananda Rivalzi; Bustami .; Rizki Suwanda (ITEJ (Information Technology Engineering Journals), 2025)
This study aims to develop a web-based hospital recommendation and mapping system utilizing Dijkstra's algorithm and the Analytical Hierarchy Process (AHP) approach. The AHP method is used to determine the best hospital based on various criteria, such as the number of inpatient rooms, number of doctors, security, hospital class type, and available facilities. Meanwhile, the shortest path to the destination is determined using Dijkstra's method to the recommended hospital. 12 hospitals served as the research subjects for a case study carried out in Lhokseumawe City. The results show that Cut Meutia Lhokseumawe Hospital is the best recommendation with the highest ranking value of 0.21. Furthermore, Dijkstra's algorithm for finding the shortest route showed that the distance from the starting point in Gampong Batuphat Timur to the recommended hospital is 17,375 meters. This developed system can assist the public in selecting the best hospital while also finding the fastest route to reach it.